Biocompatible floatable device for controlled release applications - Kwang, Guo Dong (Nanyang Technological University, 2023)
Controlled-release drug delivery systems is one research that has garnered much attention due to its ease of administration and ability to reduce frequent dosing. To address the issue on encapsulation of the wide range of chronic medical drugs, a versatile, safe, and biocompatible encapsulation system is desired. Hydrogel Platform Raft Systems (HPRS) is one of many encapsulation systems used for controlled release of drugs or chemical compounds. Few research was done on developing them as potential versatile drug sleeves to resolve issues on loading various drug types and forms. By blending two or more hydrogels to form an interpenetrating network or dual gel network, properties of HPRS can be tailored to fabricate Gastroretentive Drug Delivery Systems (GRDDS) that enables greater ease of drug encapsulation while increasing drug compatibility. Herein, a novel system using Kappa-Carrageenan (KC) and Alginate (Alg) hydrogel blend to fabricate both a dry gel raft, as a drug sleeve, and a preliminary 3D printed soft gel as an oral drug delivery device is developed. To create the low-density GRDDS, KC and Alg, with synergetic compatibility, were mixed to form an Interpenetrating Polymer Network (IPN) hydrogel with a highly porous gel structure. Coconut oil was added to further reduce the raft’s density, with CaCO3 as well to provide Ca2+ ions and CO2 for in situ crosslinking and effervescence to further enhance floatability respectively. The developed receptacle system has demonstrated drug loading compatibility for both hydrophilic and hydrophobic drug types: Carbidopa (CD) and Levodopa (LD) in initial trials, and Metoprolol Tartrate (MT) and Risperidone (Ris) used herein for release kinetic analysis. The raft was also shown capable of loading the four drugs in four forms - tablet, free drug, and secondary matrix encapsulation in microparticles and fibre mesh. The release kinetic data of both MT and Ris were also plotted and modelled after Higuchi and Korsmeyer– Peppas, and to derive an empirical formula to predict a drug’s release constant based on its logP. As compared to previous designed raft systems with lower loading compatibility the fabricated drug sleeve is capable extended floatation of over a month, and offers promising potential for use as a fully edible, week-long GRDDS with high compatibility for different drug types and forms.